Outcome Instruments in Spinal Trauma Surgery: A Bibliometric Analysis. (December 2016) - Cutler, Holt S.; Guzman, Javier Z.; Connolly, James; Al Maaieh, Motasem; Skovrlj, Branko; Cho, Samuel K.
Study Design: Literature review. Objective: To identify outcomes instruments used in spinal trauma surgery over the past decade, their frequency of use, and usage trends. Methods: Five top orthopedic journals were reviewed from 2004 to 2013 for clinical studies of surgical intervention in spinal trauma that reported patient-reported outcome instruments use or neurologic function scale use. Publication year, level of evidence (LOE), and outcome instruments were collected for each article and analyzed. Results: A total of 58 studies were identified. Among them, 26 named outcome instruments and 7 improvised questionnaires were utilized. The visual analog scale (VAS) for pain was used most frequently (43.1%), followed by the Short Form 36 (34.5%), Frankel grade scale (25.9%), Oswestry Disability Index (20.7%) and American Spinal Injury Association Impairment Scale (15.5%). LOE 4 was most common (37.9%), and eight LOE 1 studies were identified (10.3%). Conclusions: The VAS pain scale is the most common outcome instrument used in spinal trauma. The scope of this outcome instrument is limited, and it may not be sufficient for discriminating between more and less effective treatments. A wide variety of functional measures are used, reflecting the need for a disease-specific instrument that accurately measures functional limitation in spinal trauma.